The effects of N-acetyl cysteine on bacterial translocation in intestinal ischemia-reperfusion damage in rats - Bayar, M; Ilhan, Y (Medimond Publishing Co, 2004)
The study included 28 Wistar albino rats. The rats were allocated into three groups. Group I no surgical procedure was applied. In Groups II and III A. mesenteric superior was dissected and laid. Intestinal ischemia (30 min) and reperfusion (30 min) was performed. In Group II were given serum physiologic, while in Group III were given intra-peritoneal N-acetyl cysteine (100mg/kg) 45 minutes before ischemia. Plasma malondialdehyde and Glutathione peroxidase were investigated. Bacterial translocation was identified by polymerase chain reaction. Bacterial isolation was found significantly higher in Groups II and III than in the control group. After reperfusion, plasma MDA and Gpx levels in Groups II and III were increased, than in the Group I. It was found that administration of N-acetyl cysteine before ischemia in experimentally was effective in the prevention of bacterial translocation.
39th Congress of the European-Society-for-Surgical-Research -- MAY 12-15, 2004 -- Athens, GREECE
Keywords: Failure